Pengaruh Daya Tarik Pesan Promosi Penjualan, Endorsement Beauty Influencer Terhadap Minat Beli Followers Instagram Rose All Day - Jessica A Larasati; Daniel Susilo (Jurnal Spektrum Komunikasi, 2022)
The extensive use of social media by Indonesian marketers has encouraged local cosmetic company, Rose All Day Cosmetics, to use Instagram as a sales promotion and endorsement platform. Petty & Cacioppo's Elaboration Likelihood Model (ELM) theory is used in this study, such as the attractiveness theory of promotional messages, endorsement theory, and buying interest theory. These conditions underlie this research which aims to see whether the attractiveness of sales promotion messages, endorsements from beauty influencers have an impact on buying interest. This research is a quantitative explanatory study that relies on surveys as a data collection tool. Questionnaires were distributed to the study population via Instagram's direct message feature to the 102,000 followers of the account, who used the Yamane formula for Rose All Day Cosmetics. This study uses a non-probability sampling technique called purposive sampling, which involves selecting 398 people who meet predetermined criteria. Multiple linear regression is the data analysis method used in this study. The researcher found that the attractiveness of sales promotion messages on the Rose All Day Cosmetics Instagram account and endorsements by beauty influencers had a significant effect on followers' purchase intentions up to 53.2 percent, with the remaining 48.7 percent influenced by factors outside the study. However, these two variables have a significant effect on followers' purchase intentions. In conclusion, the attractiveness of sales promotion messages and endorsements has a significant effect on followers' buying interest partially or simultaneously on each of the variables studied